Studi Efisiensi Lebar Alas Dinding Penahan Tanah Tipe Kantilever pada Jalan Brigjend Abdul Manan Wijaya Kecamatan Pujon Kabupaten Malang - Vendelinus Agar; Suhudi Suhudi; Andy Kristafi Arifianto (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2020)
The method used to control the stability of the soil so that it does not experience landslides is by building a retaining wall. The construction of a retaining wall aims to maintain infrastructure and infrastructure plans to remain safe against rolling, shearing and carrying capacity of the land along the wall lines of the land for a long time (structurally strong) is a demand that must be carried out to protect the infrastructure from its failure. This research was carried out in several stages, starting from the preparation stage, collecting primary data, namely survey methods, measurements, documentation, laboratory experiments (soil types) and secondary data namely work drawings, location maps, list of unit prices needed in the analysis. Data analysis and steps in this study are: determining location, collecting data, through primary data and secondary data in supporting literature such as collecting and processing data, determining the type of soil, determining the type of retaining wall, determining the dimensions of the retaining wall, calculate the stability of rolling, shear and bearing capacity of the soil, calculate the budget plan against the dimensions of a stable retaining wall, draw details of the planned retaining wall planned. From the results of analysis of calculations and discussion of the Width of the Cantilever Type Ground Retaining Wall on street Brigjend Abdul Manan Wijaya, Pujon Subdistrict, Malang Regency can be concluded as follows: height (h) = 7.00 m, width of width (b) = 2 , 5 m, the width of the retaining wall = 0.4 m, foundation depth = 1 m, total height = 8.00 m and the total cost design for the construction of cantilever type retaining wall = Rp. 226,000,000.00. ABSTRAKSalah satu metode yang digunakan agar stabilitas tanah tidak terganggu adalah dengan membangun perkuatan dinding penahan tanah. Perencanaan  dinding penahan tanah, mempunyai tujuan guna menjaga bangunan tersebut aman terhadap guling, geser dan daya dukung tanah sepanjang garis dinding penahahan tanah tersebut. Penelitian ini dilakukan dalam beberapa tahapan, mulai dari tahap persiapan, pengumpulan data primer (survei, pengukuran, dokumentasi, analisis tanah di laboratorium) dan data sekunder (gambar kerja, peta lokasi, daftar harga satuan) yang di perlukan dalam analisis. Data primer dan data sekunder diperlukan guna mendukung penelitian ini seperti mengumpulkan dan mengolah data, menentukan jenis tanah, menentukan jenis dinding penahan tanah, menentukan dimensi dinding penahan tanah, menghitung stabilitas tanah, menghitung rencana anggaran biaya terhadap dimensi dinding penahan tanah yang stabil, gambar detail dinding penahan tanah yang direncanakan. Dari hasil analisa dan pembahasan mengenai lebar alas dinding penahan tanah tipe kantilever di Jalan Brigjend Abdul Manan Wijaya, Kecamatan Pujon, Kabupaten Malang dapat disimpulkan bahwa: tinggi (h) = 7,00 m, lebar pandasi (b) = 2,5 m, lebar atas dinding penahan = 0,4 m, kedalaman pondasi = 1 m, tinggi total = 8,00 m dan total dana yang dibutuhkan untuk perencanaan dinding penahan tanah tipe kantilever = Rp. 226.000.000,00. Kata Kunci : studi efisiensi; dinding penahan; tipe kantilever